Exporting by Mail - An Innovative Trade Facilitation Tool - Guasch, J. Luis (World Bank, Washington, DC, 2012)
There are many firms mostly -micro and small- that are de facto excluded from the export chain by virtue of their location (operating in small villages or cities with minimum or no support for export services), information (knowing what it takes and how one exports), cost of export services (need to use customs and logistics agents), lack of knowledge of proper packaging, etc. The author solution was to design a new tool that would tackle all of those problems. This tool is exporting by mail.